Integrating robotic ball launchers in table tennis: An analytical approach to stroke performance - Ibnu Fatkhu Royana; Danang Aji Setyawan; Dikna Zidhan Salman Alfarisi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Limited access to affordable and consistent ball-feeding technology remains a practical challenge for table tennis training in schools and grassroots sports programs, particularly in resource-constrained environments. This study developed and preliminarily evaluated “Robopoly,” a low-cost table tennis ball launcher engineered from repurposed fan motors to support structured technical training. Its novelty lies in a sustainable mechanical design intended as an affordable alternative to commercial robotic systems. The development process included needs assessment, prototype development, expert validation, product refinement, and preliminary field testing. Content validity, assessed by four experts using Aiken’s V Index, yielded a mean score of 0.78, classified as feasible. A pre-experimental one-group pretest–posttest design involving 10 athletes was used to assess forehand and backhand stroke accuracy. The paired-samples t-test indicated improvements in forehand accuracy, t(9) = −4.25, p = .002, Cohen’s d = 1.34, and backhand accuracy, t(9) = −3.98, p = .003, Cohen’s d = 1.26. These findings provide preliminary evidence of short-term improvements in stroke accuracy following the use of Robopoly and indicate its potential to support consistent and repeatable ball-feeding practice in resource-constrained educational and community sport settings. However, the absence of a control group limits causal interpretation. Further controlled studies with larger samples and longer follow-up periods are needed to establish the effectiveness and longer-term training effects of the device.